THE CHALLENGES OF BRAZILIAN EDUCATION IN THE FACE OF THE SANITARY CRISIS IMPOSED BY THE EMERGENCE OF CORONAVIRUS-COVID-19: APPROACH TAKEN AT MARIA RAIMUNDA MOTA DE ANDRADE STATE SCHOOL - de Souza Cazaes, Gilson (Revista Gênero e Interdisciplinaridade, 2024)
The present work has the main objective of analyzing, together with the facts that have occurred in the last few months, the behavior adopted by the Brazilian educational system in the face of the immense challenge presented by the spread of a global level and reach pandemic, which has started to hit head on, not only the educational system of Brazilian education, but also the whole modus vivendi of our unexpected challenge, which demanded, and still requires, urgent decisions and as far as possible, correct, since for catastrophes and pandemics there are no ready-made formulas, but extreme decisions.